X-Linked Agammaglobulinemia Presenting with Secondary Hemophagocytic Syndrome: A Case Report. (21st January 2013) - Ozturk, Can; Sutcuoglu, Sumer; Atabay, Berna; Berdeli, Afig
Abstract : Introduction . Coincidence of X-linked agammaglobulinemia (XLA) and secondary hemophagocytic syndrome (sHS) is atypical. Both diseases are rare and pathogenesis of the latter one is not clearly known. Case Presentation . A 5-year-old boy was diagnosed both with XLA and sHS. However, in his history, he did not have severe and recurrent infections. Bruton tyrosine kinase (BTK) gene mutation was present (c.1581_1584delTTTG). To the best of the authors' knowledge, coincidence of XLA and sHS had not been reported in the literature before. Conclusion . Patients with XLA are extremely vulnerable to recurrent bacterial infections. The diagnosis of XLA with sHS at any time of life is both an interesting and challenging situation without history of recurrent bacterial infections.